2022
DOI: 10.3389/fendo.2022.888557
|View full text |Cite
|
Sign up to set email alerts
|

Total Diet Replacement Within an Integrated Intensive Lifestyle Intervention for Remission of Type 2 Diabetes: Lessons From DiRECT

Abstract: The prognosis for people with type 2 diabetes (T2D) remains concerning, yet its seriousness is often underestimated. T2D is a manifestation, in susceptible individuals, of the disease-process of obesity, and at diagnosis, 10-year survival rates for T2D are around 50%. Here, we will examine: (a) the role of weight loss in T2D, (b) use of total diet replacements (TDRs) to induce weight loss, (c) the Diabetes Remission Clinical Trial (DiRECT) protocol and key results, (d) other dietary interventions related to T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…When compared with baseline results, the mean BMI of men with the highest adherence to this pattern remained stable (26.1 kg/m 2 , before and after) and there was no significant increase in the proportion of men with overweight or obesity ( Table S4 ). These findings are very promising, as one of the primary strategies for diabetes remission is weight loss of >10% of body weight [ 43 ]. In our sample we observed an improvement in glycemic control without changes in body weight, suggesting that the diet composition itself may have a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with baseline results, the mean BMI of men with the highest adherence to this pattern remained stable (26.1 kg/m 2 , before and after) and there was no significant increase in the proportion of men with overweight or obesity ( Table S4 ). These findings are very promising, as one of the primary strategies for diabetes remission is weight loss of >10% of body weight [ 43 ]. In our sample we observed an improvement in glycemic control without changes in body weight, suggesting that the diet composition itself may have a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Current gaps in this area of research include identifying the type of formulations and complimentary aspects of a dietary program that yield long-term weight loss maintenance, reduce cardiometabolic risk, and increase the odds of diabetes remission in overweight and obese patients with type 2 diabetes. In this special issue in the Frontiers of Endocrinology , we comment on three key perspective articles that outline (1) the role for diabetes-specific nutrition formulas (DNSFs) as meal replacements in type 2 diabetes management ( 6 ), (2) lessons learned from the Diabetes Remission Clinical Trial (DiRECT) which demonstrated diabetes remission with the use of TDR followed by structured food reintroduction and long-term weight loss maintenance ( 7 ), and (3) use of meal replacements as a temporary option to induce weight loss followed by transition to a dietary pattern that aligns with the values, preferences and treatment goals of the patient ( 8 ). In the first article, Noronha and Mechanick highlight that DSNFs can be used to deliver essential macro- and micronutrients that align with the core nutrition principles from clinical practice guidelines for diabetes prevention and management ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the second article, Noronha et al. discuss how body fat accumulation is the dominant driver of type 2 diabetes, and therefore recommend weight loss as the best solution to reduce progression from prediabetes to type 2 diabetes or to achieve remission of type 2 diabetes ( 7 ). For remission to occur, weight loss of > 15 kg is generally needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations